. Diagnostic Levels of C-reactive protein (CRP), epinephrine (Ep), cortisol (Cor), and norepinephrine (NE) in Patients Undergoing Laparoscopic Surgery for Gallstones receiving Anti-inflammatory: Diagnostic Levels of C-reactive protein (CRP), epinephrine (Ep), cortisol (Cor), and norepinephrine (NE) - Wang, Gaoqiang (Journal of Medical Biochemistry, 2025)
Objective: To investigate the effect of anti-inflammatory and choleretic soup on CRP, E, Cor, NE and gallbladder function recovery in patients after laparoscopic cholecystectomy. Methods: 111 patients with gallstones who underwent laparoscopic surgery in the hospital from November 2019 to March 2024 were selected, and all patients were separated into two groups adoptting the random number method. The control group (n=56) received extracorporeal circulation treatment alone; The experimental group (n=55) were combined with the application of anti-inflammatory bile soup on its basis. Finally, to compare and analyze the differences in the levels of C-reactive protein (CRP), epinephrine (Ep), cortisol (Cor), and norepinephrine (NE) between the two groups, and evaluate the effect of gallbladder function recovery. Results: Three months after treatment, the levels of CRP, Ep, Cor, and NE in both groups decreased compared with those before the experiment, and the levels of each index in the experimental group were lower than those in the control after treatment (P
Keywords: Gallstones; Laparoscopy; Anti-inflammatory bile soup; C-reactive protein; Epinephrine; Cortisol; Norepinephrine